2019
DOI: 10.1101/686725
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Chemogenetic silencing of neurons in the mouse anterior cingulate area modulates neuronal activity and functional connectivity

Abstract: 29The anterior cingulate area (ACA) is an integral part of the prefrontal cortex in mice and has been 30 implicated in several cognitive functions. Previous anatomical and functional imaging studies 31 demonstrated that the ACA is highly interconnected with numerous brain regions acting as a hub region 32 in functional networks. However, the importance of the ACA in regulating functional network activity and 33 connectivity remains to be elucidated. Recently developed neuromodulatory techniques, such as Design… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…Using the Frontal, RSC-HIPP, and Association modules ROIs (one-sample t-test, P < 0.0001) and striatum as a reference region due to sparse LC-NE neuron innervation, we examined how NE release from LC modulates fMRI-derived CBV, regional homogeneity (ReHo) (40) and amplitude of low frequency fluctuation (ALFF) (41) changes. We compared a 10 min baseline fMRI data prior to administering CNO against data acquired between 20-30 min post-CNO to account for DREADD-induced activity kinetics reported in fMRI (8,(42)(43)(44)(45) and behavior studies (30,31).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Using the Frontal, RSC-HIPP, and Association modules ROIs (one-sample t-test, P < 0.0001) and striatum as a reference region due to sparse LC-NE neuron innervation, we examined how NE release from LC modulates fMRI-derived CBV, regional homogeneity (ReHo) (40) and amplitude of low frequency fluctuation (ALFF) (41) changes. We compared a 10 min baseline fMRI data prior to administering CNO against data acquired between 20-30 min post-CNO to account for DREADD-induced activity kinetics reported in fMRI (8,(42)(43)(44)(45) and behavior studies (30,31).…”
Section: Resultsmentioning
confidence: 99%
“…S4, B and C Using the Frontal, RSC-HIPP, and Association module ROIs (one-sample two-sided t-test, P < 0.0001) and striatum as a reference region due to sparse innervation from LC-NE neurons, we examined how NE release from LC modulates fMRI-derived CBV, regional homogeneity (ReHo) and amplitude of low frequency fluctuation (ALFF) changes. We compared the 10 min, pre-CNO baseline fMRI data against data acquired between 20-30 min post-CNO to account for CNOinduced activity kinetics reported in fMRI (6,(37)(38)(39)(40)(41) and behavior studies (29,30). CNO-evoked LC-NE activation significantly decreased CBV in all DMN modules in LC-NE/hM3Dq (unpaired t test, PFDR-corrected < 0.05) but not in control mice (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chemogenetic-fMRI can provide important information about the effects of particular nodes in the brain on whole brain activity and connectivity within specific networks ( Giorgi et al., 2017 ; Peeters et al., 2020 ). In this study, excitatory DREADDs were expressed in the right BFB cholinergic neurons of rats and the effects of DREADDs-induced neural activity alterations were evaluated by means of non-invasive rsfMRI.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, our group expressed inhibitory KORD in the anterior cingulate area and used BOLD functional MRI to evaluate its effect on neuronal activity and functional connectivity. We observed that inhibition of the anterior cingulate area, which has been identified as a hub region (i.e., a highly interconnected brain region), resulted in large‐scale neuronal activity modulations as well as functional connectivity alterations (Peeters et al, ). Furthermore, other recent studies combined chemogenetics with resting‐state functional MRI in order to evaluate functional connectivity alterations after modulation of the excitation–inhibition balance in the somatosensory cortex (Markicevic et al, ) or to assess the effects of selective stimulation of the locus coeruleus with hM3Dq on a large‐scale functional connectivity (Zerbi et al, ).…”
Section: Dreadds Combined With Imaging Techniquesmentioning
confidence: 99%